Academic misconduct: Evidence from online class - Kiky Srirejeki; Agung Praptapa; Bambang Setyobudi Irianto; Agus Faturokhman (International Journal of Evaluation and Research in Education (IJERE), 2022)
Academic misconduct has been a recurrent issue in higher education. The advent of online learning during the Coronavirus disease 2019 (COVID-19) pandemic has undoubtedly spurred concern about the spike in academic misconduct. This study explored the attitude of accounting students toward various issues when taking online learning during the pandemic, which included: i) Types of academic misconduct being committed; and ii) The extent of academic misconduct likelihood during online learning. Based on a qualitative survey of 182 accounting students from three prominent state universities in Indonesia, results suggested that students engage in multiple types of academic misconduct. The students’ likelihood to commit academic misconduct is higher during online learning than in offline learning. The implication of such findings is briefly discussed.